2002
DOI: 10.1103/physrevc.66.044615
|View full text |Cite
|
Sign up to set email alerts
|

Intranuclear cascade model for a comprehensive description of spallation reaction data

Abstract: A new version of the Liège intranuclear cascade ͑INC͒ model is proposed for the description of spallation reactions. Compared to the previous version, it incorporates new features: ͑i͒ it can accommodate a diffuse nuclear surface, ͑ii͒ the treatment of the Pauli blocking effect is improved, removing unphysical features linked with the use of statistical blocking factors, ͑iii͒ collisions between moving spectator nucleons are explicitly suppressed, ͑iv͒ pion dynamics is improved, especially concerning the delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
498
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 380 publications
(523 citation statements)
references
References 66 publications
(1 reference statement)
18
498
2
5
Order By: Relevance
“…Figs. 14 and 15 show two examples by this preliminary version of LAQGSM03.03F, namely, spectra of 6,7,8,9 Li at 65 • from proton-gold interactions at 1.2 and 1.9 GeV, respectively. This preliminary version of LAQGSM03.03F describes quite well spectra of all Li fragments measured for these reactions by the PISA collaboration and published in Ref.…”
Section: Laqgsm Extensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figs. 14 and 15 show two examples by this preliminary version of LAQGSM03.03F, namely, spectra of 6,7,8,9 Li at 65 • from proton-gold interactions at 1.2 and 1.9 GeV, respectively. This preliminary version of LAQGSM03.03F describes quite well spectra of all Li fragments measured for these reactions by the PISA collaboration and published in Ref.…”
Section: Laqgsm Extensionmentioning
confidence: 99%
“…At lower energies, MCNP6 uses tables of evaluated nuclear data (referred to as "data libraries"), while for higher energies (> 150 MeV), MCNP6 uses CEM03.03 and LAQGSM03.03 as mentioned above, as well as by default for some reactions, or when chosen by users, the Bertini intranuclear cascade (INC) [7], ISABEL [8], or the INC developed at Liege (INCL) by Cugnon and colleagues from CEA/Saclay, France, version INCL4.2 [9], merged with the evaporation/fission and Fermi break-up models available in MCNP6 (see details in [1]). Emission of energetic heavy clusters from nuclear reactions plays a critical role in several applications, including electronics performance in space, human radiation dosages in space or other extreme radiation environments, proton and heavy-ion therapy in cancer treatment, accelerator and shielding applications, and more.…”
Section: Introductionmentioning
confidence: 99%
“…[4] for a detailed description of the standard version (INCL4.2) of the INCL4 model. It is sufficient here to remind the salient features.…”
Section: A Brief Description Of the Incl42 Modelmentioning
confidence: 99%
“…6 GeV range. A recent intercomparison of models, organized by the IAEA [3], has shown that the intranuclear cascade model developed at the University of Liège, denoted INCL4 [4], coupled to the evaporation-fission ABLA model of K.-H. Schmidt [5,6], can describe quite well a huge body of experimental data for proton-induced reactions in the 100 MeV-2 GeV range. This includes total reaction cross sections, neutron multiplicities, neutron and proton double differential cross sections, residue mass spectra, isotopic distributions and recoil energies.…”
Section: Introductionmentioning
confidence: 99%
“…The Liège Intranuclear Cascade model, INCL4 [1], has originally been developed to describe spallation reactions, i.e. nucleon-induced collisions in the 100 MeV -3 GeV energy range.…”
Section: Introductionmentioning
confidence: 99%